Study on Transmission Error of Cylindrical Gear with Arcuate Tooth Trace - Ma Dengqiu; Ye Zhenhuan; An Yu; Wu Tingqiang; Chen Fangzhou (Jixie chuandong)
In order to study the transmission error of the cylindrical gear with arcuate tooth trace，a torsional vibration model of the cylindrical gear with arcuate tooth trace transmission system is proposed，and a dynamics model is established based on 3D model.The influence of tooth width，tooth line radius，load and rotation speed on the transmission error is analyzed.The results show that，the transmission error fluctuates periodically around 0 when the structure parameters and working conditions are different； the transmission error amplitude decreases first and then increases with the increase of the tooth width； the transmission error amplitude changes in shape of “W” with the increase of the tooth line radius，that is，it first decreases and then increases with the increase of the tooth line radius，and then first decreases and then increases with the increase of the tooth line radius； the transmission error amplitude increases with the increase of load and rotating speed.The results provide the theoretical basis for the noise reduction and lubrication，fault diagnosis and gear tooth geometric modification of the cylindrical gear with arcuate tooth trace.